TECHNICAL, ECONOMIC AND LEGAL ASPECTS REGARDING THE IMPLEMENTATION OF HOLIDAY TICKETS - Romeo Cătălin CREȚU; Petrică ȘTEFAN; Ioan Iulian ALECU; Cătălin Constantin VOINEA-MIC; Iulian MUNTEAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Holiday tickets (or holiday vouchers) are value vouchers, similar to meal vouchers, which can be offered by employers to employees. They serve as a payment instrument for payment of tourist services/holidays exclusively in Romania, for the beneficiary and his/her family. Holiday vouchers are nominal and non-transferable, they are deductible and tax-free, both for the employer and for the employee. In this paper, we analyzed the legal framework for the issue and implementation of holiday vouchers, as well as economic issues related to the effects on the increase in the number of tourists and the revenues from tourism. At the same time, we analyzed the influence of introducing holiday vouchers on the decrease in unauthorized tourism in our country. To make these studies, we have used statistical data provided by The Ministry of Tourism, The National Institute of Statistics, „The Federation of Hotel Industry of Romania” (FIHR) and by „The National Association of Tourism Agencies” (ANAT). We also analyzed and interpreted a survey conducted by the Romanian Hoteliers Federation among tourists, employers, tour operators and travel agencies. According to the data, the granting of holiday allowances or holiday bonuses in the form of holiday vouchers of 1,450 RON between 1 July 2017 and 30 November 2018 allowed 1.2 million Romanians, employees of state institutions or companies in which the state is a sole or majority shareholder, to spend their holidays in the country. At the end of October 2018, the value of holiday vouchers increased to EUR 244 million, 8.4 times higher than in 2017.